Interview with Haud Guéguen, Pierre Sauvêtre and Christian Laval: The choice of civil war. Another history of neoliberalism (Geografares, 2021)
Translation of the French interview published in the Diacritik Magazine on April 22, 2021 and performed by Alexis Pelletier with Haud Guéguen, Pierre Sauvêtre and Christian Laval, three of the four authors (the other author is Pierre Dardot) from the book The Choice of Civil War. Another history of neoliberalism, published in French by Lux Éditeur in April 2021 and soon to be launched in Brazil by the publisher Elefante